Strategic plan for Rosario's Fresh and Processed Fruits - Lopez, Rodgessa A. (School of Management, University of the Philippines Mindanao, 2010)
The company started in the 1990s, Rosario?s Fresh and Processed Fruits is owned and managed by the Belviz family. The company is engaged mainly in the production and processing of Durian fruit although there are also various fruit trees at experimental growing stage. Currently, the company cultivates ten hectares of land and leases a twenty-hectare farm in Calinan, Davao City with full-grown Durian trees. After ten years of farming, the management discovered that there is an ample amount of fruit rejects, which can still be processed to lessen wastage. Hence, the processed section started by minimally and manually processing the fruit. In 2006, the company acquired machines for faster and more efficient production. In 2008, the company was awarded as the best MSME in 2008 at the micro-level. Management framework of Fred R. David was used to formulate strategies, assess the company?s objectives and the implementation and control of these strategies. This will result to a strategic plan that will be implemented in the next five years based on the different factors that will affect the company?s productivity and profitability. Factors include the external and internal environments resulting to findings that had been quantified using SWOT matrix and QSPM. This enabled the management to arrive at logical strategic option for the business. Result of the analysis showed the company has yet to take advantage of the opportunities in the Durian industry with its strong internal position. The suggested strategies for the next five years are Product Development, Market Penetration and Market Development. The implementing programs start with setting of objectives and targets and identifying measures & initiatives to ensure that the activities will be carried out. In 2010, the company will acquire Good Manufacturing Practices (GMP) certification to become competitive in the food processing sector, develop new products that are appealing to the customers mainly in Region XI market, penetrate the market through promotions and establishing contacts. The fresh section shall establish strong documentation systems and proper accounting. By 2012, it will venture into market development through market study in other regions of the country. This is great challenge for the management of Rosario?s to be competitive in the industry although data monitoring for Durian is scarce. Knowledge, skill and assistance by government agencies and research institutions will catalyse improvement of Durian production and processing.